Ab initio study of negative electron affinity on the scandium-terminated diamond (100) surface for electron emission devices. (30th August 2022) - Zulkharnay, Ramiz; Allan, Neil L.; May, Paul W.
Abstract: Surface modification of diamond with the addition of (sub)monolayer of metals or other electropositive adsorbates than the bulk carbon can result in negative electron affinity (NEA). Surface coverages of up to one-monolayer (<1 ML) of scandium on clean, oxygenated and nitrogenated diamond (100) surfaces were studied via plane-wave density functional theory (DFT) calculations. Adsorption of Sc on diamond is energetically favourable; for example, 0.25 ML coverage of Sc on the oxygenated diamond (100) surface has an extremely large calculated adsorption energy per adsorbate atom of −8.68 eV. Moreover, the majority of stable Sc-adsorption configurations possess NEA, with the most negative values of −3.73 eV, – 3.02 eV and −1.75 eV being found for 0.25 ML Sc coverage on the oxygenated, bare and nitrogenated diamond surfaces, respectively. These results predict that Sc termination on diamond should provide a thermally stable surface with large NEA, and is therefore a highly promising candidate for thermionic and other electron-emission applications. Graphical abstract: Image 1